Issues Improvement Management of Production Enterprises - Sabirovich, Kazakov Olim (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article studies the issues of improving the management of manufacturing enterprises in the context of the globalization of the economy. The main directions for improving the management of manufacturing enterprises are proposed.